(Invited) Electrodeposition in Microporous Silicon from the Viewpoint of Hydration Property: Effect of Coexisting Ions in Zinc Electrodeposition. (18th September 2015) - Fukami, Kazuhiro; Koda, Ryo; Koyama, Akira; Sakka, Tetsuo; Abe, Takeshi; Kitada, Atsushi; Murase, Kuniaki
Abstract : Electrodeposition of zinc in nanoporous silicon electrodes was studied in detail. In an earlier study, we have reported that coexisting counter ions have an impact on electrodeposition behavior of platinum within nanoporous silicon. In the present study, we investigate that the effect of counter ions on zinc electrodeposition within nanoporous silicon. It has been clarified that the deposition behavior of zinc is dependent upon the counter anions. The deposition behavior is discussed based on the density of nucleation at the initial stage of the deposition.